Opening Iapetus: Constraints from the Laurentian margin in Newfoundland - Cawood, Peter Anthony; McCausland, P J A; Dunning, G R (2001)
Late Neoproterozoic to Early Cambrian geologic, geochronologic, and paleomagnetic data from along the Iapetus margin of Laurentia may be reconciled,within a multistage rift history that involved an initial separation of Laurentia from the west Gondwana cratons ca. 570 Ma, followed by rifting of a further block or blocks from Laurentia ca 540-535 Ma into an already open Iapetus Ocean to establish the main passive-margin sequence in the Appalachians. Paleomagnetic data suggest that Laurentia rifted from Amazonia-Rio de la Plata cratons and began its northward movement ca. 570 Ma to produce a wide Iapetus Ocean by 550 Ma. Geologic data from the Newfoundland segment of the Laurentian margin provide evidence for a rift-drift transition ca. 540-535 Ma, as constrained by the youngest rift-related magmatism at 550.5 (+3)/(-2) Ma (U/Pb zircon) for the Skinner Cove Formation and 555 (+3)/(-5) Ma for the Lady Slipper pluton, and a late Early Cambrian age of ca, 525-520 Ma for the oldest drift-related sedimentation. Rifting between the Laurentia and the west Gondwana cratons was probably distributed among multiple rift systems that fostered the production of a number of terranes (such as the Argentine Precordillera, Oaxacan) as well as the Iapetus Ocean. Development of Laurentian-derived Iapetan terranes during the final breakout of Laurentia from Rodinia may have been facilitated by preexisting 760-700 Ma rift weaknesses and apparently rapidly changing plate vectors during latest Neoproterozoic time.